Study of the Friction Stir Welding For A516 Low Carbon Steel (Journal of Engineering, 2014)
The main objective of present work is to describe the feasibility of friction stir welding (FSW) forjoining of low carbon steel with dimensions (3 mm X 80 mm X 150 mm). A matrix (3×3) of weldingparameters (welding speed and tool rotational speed) was used to see influence of each parameter onproperties of welded joint .Series of (FSW) experiments were conducted using CNC milling machineutilizing the wide range of rotational speed and transverse speed of the machine. Effect of weldingparameters on mechanical properties of weld joints were investigated using different mechanical testsincluding (tensile and microhardness tests ). Micro structural change during (FSW) process wasstudied and different welding zones were investigated using optical microscope. The stir weldingexperiments conducted that show the low carbon steel can be welded using (FSW) process withmaximum welding efficiency (100.02%) in terms of ultimate tensile strength using best result ofwelding parameters (700 RPM, 25 mm/min, tool rotational speed and welding speed respectively and0.2 mm plunging depth of welding tool) ,there is afirst time that we obtain the efficiency reach to100.02 % to weld this type of low carbon steel by FSW. The corrosion resistance was measure whichis the new test on the welding by this way and we obtained different result from the result ontraditional welding processes and the result that obtained show the corrosion resistance for thiswelding plate better than the base metal. Maximum temperature has been calculated numerically byusing the ANSYS program. The obtained peak temperature is 1102°C, A percentage minimum of themelting point .